Financial Integration in Latin America. (Policy Papers; Policy Paper ;, 2016)
Many Latin American economies have experienced significant reductions in growth recently, as a result of the end of the commodity super-cycle and the rebalancing of China's growth, and a number of global banks have been leaving the region. AlthoughLatin American countries were generally less affected by the global financial crisis (GFC) than other regions, the region continues also to suffer from the protracted sluggish growth in advanced economies. In addition, there has since 2008 been a withdrawal of global banks from the region, thus potentially worsening access to credit or reducing competition in the financial sector. More broadly, the GFC demonstrated that extreme economic volatility can originate from outside the region, rather than internally, as was the experience of the 1980s and 1990s...